Metagenome-based diversity analyses suggest a significant contribution of non-cyanobacterial lineages to carbonate precipitation in modern microbialites - Saghaï, Aurélien; Zivanovic, Yvan; Zeyen, Nina; Moreira, David; Benzerara, Karim; Deschamps, Philippe; Bertolino, Paola; Ragon, Marie; Tavera, Rosaluz; López-Archilla, Ana I.; López-García, Purificación (Frontiers in Microbiology, 2015)
Cyanobacteria are thought to play a key role in carbonate formation due to their metabolic activity, but other organisms carrying out oxygenic photosynthesis (photosynthetic eukaryotes) or other metabolisms (e.g., anoxygenic photosynthesis, sulfate reduction), may also contribute to carbonate formation. To obtain more quantitative information than that provided by more classical PCR-dependent methods, we studied the microbial diversity of microbialites from the Alchichica crater lake (Mexico) by mining for 16S/18S rRNA genes in metagenomes obtained by direct sequencing of environmental DNA. We studied samples collected at the Western (AL-W) and Northern (AL-N) shores of the lake and, at the latter site, along a depth gradient (1, 5, 10, and 15 m depth). The associated microbial communities were mainly composed of bacteria, most of which seemed heterotrophic, whereas archaea were negligible. Eukaryotes composed a relatively minor fraction dominated by photosynthetic lineages, diatoms in AL-W, influenced by Si-rich seepage waters, and green algae in AL-N samples. Members of the Gammaproteobacteria and Alphaproteobacteria classes of Proteobacteria, Cyanobacteria, and Bacteroidetes were the most abundant bacterial taxa, followed by Planctomycetes, Deltaproteobacteria (Proteobacteria), Verrucomicrobia, Actinobacteria, Firmicutes, and Chloroflexi. Community composition varied among sites and with depth. Although cyanobacteria were the most important bacterial group contributing to the carbonate precipitation potential, photosynthetic eukaryotes, anoxygenic photosynthesizers and sulfate reducers were also very abundant. Cyanobacteria affiliated to Pleurocapsales largely increased with depth. Scanning electron microscopy (SEM) observations showed considerable areas of aragonite-encrusted Pleurocapsa-like cyanobacteria at microscale. Multivariate statistical analyses showed a strong positive correlation of Pleurocapsales and Chroococcales with aragonite formation at macroscale, and suggest a potential causal link. Despite the previous identification of intracellularly calcifying cyanobacteria in Alchichica microbialites, most carbonate precipitation seems extracellular in this system.